A framework for distributed health professions training: using participatory action research to build consensus - Van Schalkwyk, Susan C. (BMC Med Educ, 2020)
BACKGROUND: There is a global trend towards providing training for health professions students outside of tertiary academic complexes. In many countries, this shift places pressure on available sites and the resources at their disposal, specifically within the public health sector. Introducing an educational remit into a complex health system is challenging, requiring commitment from a range of stakeholders, including national authorities. To facilitate the effective implementation of distributed training, we developed a guiding framework through an extensive, national consultative process with a view to informing both practice and policy. METHODS: We adopted a participatory action research approach over a four year period across three phases, which included seven local, provincial and national consultative workshops, reflective work sessions by the research team, and expert reviews. Approximately 240 people participated in these activities. Engagement with the national department of health and health professions council further informed the development of the Framework. RESULTS: Each successive ‘feedback loop’ contributed to the development of the Framework which comprised a set of guiding principles, as well as the components essential to the effective implementation of distributed training. Analysis further pointed to the centrality of relationships, while emphasising the importance of involving all sectors relevant to the training of health professionals. A tool to facilitate the implementation of the Framework was also developed, incorporating a set of ‘Simple Rules for Effective distributed health professions training’. A national consensus statement was adopted. CONCLUSIONS: In this project, we drew on the thinking and practices of key stakeholders to enable a synthesis between their embodied and inscribed knowledge, and the prevailing literature, this with a view to further enaction as the knowledge generators become knowledge users. The Framework and its subsequent implementation has not only assisted us to apply the evidence to our educational practice, but also to begin to influence policy at a national level.